Strengthening The Tolerance And Cooperative Characterthrough Volleyball Learning - Reski Aditya Amir; Hadi Pajarianto; Suaib Nur (STKIP Muhammadiyah Kuningan, 2022)
Physical education has a significant position in national education and is very popular to become students' favourite. One of the physical education lessons is volleyball which has several potential aspects for building the student's character. This research aims to identify the strengthening of tolerance character in volleyball learning; and the strengthening of cooperative character in volleyball learning. This research method used four stages of design: planning, action and observation, reflection after the reflection, and then proceeds with re-planning, which is planned for two cycles. The results show that in cycle 1, the tolerance character is 48%, and in cycle 2 is 80%. Meanwhile, the cooperative nature in cycle 1 is 49%, and in cycle 2 is 79%. These results confirm that character strengthening can be conducted in all physical education lessons, including volleyball. Based on the results, it can be concluded that tolerance and cooperative character strengthening can be done through systematic volleyball teaching